THU0357 Prevalence of Rheumatoid Arthritis in French West Indies, an African Ancestry Population. The Eppra Study. (9th June 2015) - Debandt, M.; Banydeen, R.; Brunier, L.; Blettery, M.; Derancourt, C.; Polomat, K.; Dehlinger, V.; Arfi, S.; Deligny, C.; Merle, S.; Jean-Baptiste, G.
Abstract : Background: Rheumatoid arthritis (RA) is a disabling chronic disease, regarded as the most frequent inflammatory rheumatism in adults, with a prevalence estimated between 0.3 and 1%, and a feminine ascendancy. In metropolitan France this prevalence is estimated from 0.3% to 0.5% of the general population. No precise data is available for French West Indies, and the prevalence of RA in this population of African ancestry is poorly evaluated. Objectives: The objective of the study is to estimate RA prevalence in the FWI by a census forward-looking epidemiological survey in the hospital and liberal sectors for one year duration. Methods: It is a unique tour with clinical examination, self-administered questionnaires and declaration. Secondary objectives are description of clinical and socio economical aspects of RA and cardiovascular comorbidities. We present the results for Martinique. Our survey was widely distributed (radio, press, patients' associations…) to ensure a good completeness. Data were analysed using SAS 9.3 software (SAS Institute Inc., Cary, NC, USA). Throrough descriptive analysis of collected variables was conducted. Crude prevalence rates were adjusted to a standard population of Martinique (nationwide census in 2010). The 95% CIs were calculated using the Poisson distribution. Results: Our completeness is good. 538 RA were collected, giving a prevalence in Martinique of 0.184% of the adult population (290 000), respectively 0.049 for men and 0.292 for women. 44% of these patients are treated in private practice and 56% in hospital. This cohort is composed of 88% women and 12% men; 92% were born in Caribbean and 7.7% elsewhere. Patients self declared of Afro Caribbean origin in 92.7%, Caribbean White in 1.7%, caucasian in 3% and other in 2.1%. Their mean disease duration was 9.7±10 years. RF and ACPA were positive in 82.2% (FR+ 392, ACPA+349, 35% low level, 65% high level): CCP+FR+ in 306, FR+CCP- in 77, FR-CCP+ in 41, FR-CCP- in 96. 17% had extra articular manifestations. ACR1987 and ACR2010 criteria were pos in 94.4% and 78%. HAQ was <1 in 74%, >1and <2 in 20% and >2 in 3%. DAS28 were respectively <2.6 in 59%, <3.2 in 15.4%, <5.1 in 23% and >5.1 in 3%. Less than 5% are ever smoker. Parodontopathy is infrequent. Cardiovascular risk factors were noticed in 89, 4% with a mean of 2 CVRF beside RA. Conclusions: This work clarifies the low prevalence of RA in this population of African origin. Some characteristics as: reduced prevalence, strong female representation, strong seropositivity, high levels of anti-CCP, no tobacco, differentiate our patients from other populations and evoke another etiology than tobacco. Disclosure of Interest: None declared